Pengaruh Independensi, Integritas, Dan Kompetensi Terhadap Kinerja Auditor - Eviyany, Agnes; Lapoliwa, Narumi (Universitas Multimedia Nusantara, 2014)
The information in financial statements is used by investors, creditors, and other parties in making investment decisions. Thus auditors' performance in assuring the reliability of financial statements' information is very important to investors. The purpose of this study is to analyze the effect of independence, integrity and competence towards auditor performance. The object of this study is auditor at big four and non- big four public accounting firms in Jakarta and Tangerang. Selection of the sample in this study is determined based on convenience sampling method. The sample used in this study are auditors who work more than one year at the same position at public accounting firm. The data used in this study are primer data, questionnaires distributed to respondents (auditor). Data analysis method used is multiple regression. The result of this study are: (1) independence has significant effect towards auditor performance, (2) integrity has significant effect towards auditor performance, (3) competence has significant effect towards auditor performance, (4) independence, integrity, and competence simultaneously have significant effect towards auditor performance. Keywords: auditor, independence, integrity, competence, auditor performance